2018
DOI: 10.1007/s13246-018-0661-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical behavior of Hoffa’s fat pad in healthy and osteoarthritic conditions: histological and mechanical investigations

Abstract: The Infrapatellar Fat Pad (IFP) lies between patella, femur, meniscus and tibia and properly fills the space between these structures. This fatty structure facilitates distribution of synovial fluid and may act to absorb impulsive actions generated through the joint. In case of Osteoarthritis (OA), IFP is found to be affected by inflammation, hypertrophy and fibrosis. The aim of the present study is to analyze the correlation between microscopic characteristics and mechanical properties of the IFP in healthy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Furthermore, the IFP itself is affected by immune cells in OA; in fact, compared to healthy-IFPs, it shows an increase in inflammatory infiltration, vascularization and fibrosis with thickened interlobular septa also supported by higher levels of VEGF, MCP-1, and IL-6 proteins (Favero et al, 2017;Fontanella et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the IFP itself is affected by immune cells in OA; in fact, compared to healthy-IFPs, it shows an increase in inflammatory infiltration, vascularization and fibrosis with thickened interlobular septa also supported by higher levels of VEGF, MCP-1, and IL-6 proteins (Favero et al, 2017;Fontanella et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its interaction with different extracellular matrix proteins, which not only occur in the articular cartilage, we speculate that COMP is involved in the remodeling processes of the IPFP to fibrotic tissue. The remodeling with hypertrophy and fibrosis of the IPFP in context with high‐grade OA has been described by a few authors, and it is supposed to be a source of pain in these patients . Moreover, it seems, that the IPFP could be involved in the inflammatory reaction pathognomonic for OA, as in an animal model, the injection of arthritogenic factor led to synovitis of Hoffa's synovia, infiltration with neutrophils and mononuclear cells and fat necrosis .…”
Section: Discussionmentioning
confidence: 92%
“…The remodeling with hypertrophy and fibrosis of the IPFP in context with high-grade OA has been described by a few authors, and it is supposed to be a source of pain in these patients. 19,47 Moreover, it seems, that the IPFP could be involved in the inflammatory reaction pathognomonic for OA, as in an animal model, the injection of arthritogenic factor led to synovitis of Hoffa's synovia, infiltration with neutrophils and mononuclear cells and fat necrosis. 48 Recent studies have shown that also the IPFP secretes proinflammatory cytokines and may modulate the inflammatory processes contributing to the pathomechanism of knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, which emerging evidence implicates as a major risk factor for knee OA, induces a low‐grade systemic inflammatory state characterized by the production of adipokines and proinflammatory cytokines by adipose tissue . The infrapatellar fat pad (IPFP), also known as Hoffa's fat pad, is the main adipose structure within the knee joint, and plays a role in distributing mechanical loads within the articular joint . The IPFP has been suggested to be involved in OA pathogenesis by secreting proinflammatory cytokines (e.g., TNF‐α and IL‐6) and adipokines (adipose tissue‐derived cytokines), contributing to intra‐articular inflammation and pain .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The infrapatellar fat pad (IPFP), also known as Hoffa's fat pad, is the main adipose structure within the knee joint, 11 and plays a role in distributing mechanical loads within the articular joint. 12 The IPFP has been suggested to be involved in OA pathogenesis [13][14][15][16][17][18] by secreting proinflammatory cytokines (e.g., TNF-␣ and IL-6 14,17,[19][20][21] ) and adipokines (adipose tissue-derived cytokines), 8,22,23 contributing to intra-articular inflammation and pain. 8 Studies suggest that adipokines, including adipsin, adiponectin, and leptin, play specific roles in the development of OA.…”
Section: Introductionmentioning
confidence: 99%